The township concept in modern South Africa - Souesi, Ismini-Maria (Department of Political Studies, 2023)
This dissertation will look at the articulation and consolidation of a "township concept" in the administrative environment of early apartheid South Africa. It is argued that the concept - a joint product of two seemingly divergent discourses, ne of modem it and the other of racial- was and identified as a solution to the urban crisis of the 19ifgs. I further arguelnafthe concept of a township for the urban African population - with all that it entailed - reflects the was in which the crisis and the role of the African in the South African urban system _were perceived by policy-makers. The socio-economic environment and the intellectual context in which the concept was introduced affirmed l he relationship between space and society and the extent to which spatial solutions could resolve socio-economic problems. It is at this point those urban discourses, from urban administration to physical planning, met with the apartheid project for Separate Development. The intellectual construction of a "tribal" or "transitional" identity which normalised exclusion from the sphere of social interaction in the cities was permanently ingrained in the urban tapestry through the racialisation of town planning. The spatial model of the township attests to a congruence in the processes by which urban Africans were to be governed and the ways in which urban resistance was to be suppressed through a reinterpretation of the urban subject as a member of a geographically and socially contained community. The administrative model contained within the township concept was to reinforce the discipline imposed by the spatial model (through the marginal location of the township, ethnic zoning, and single-storey houses) with the use of housing provision as a mechanism for influx control and the constitution of structures of government supportive of Separate Development.